DUAL FREQUENCY ANTENA MIKROSTRIP - Surjati, Indra (Jurnal Teknik Elektro, 2003)
This research showed that microstrip antenna can be worked at two different frequencies.This different frequency with low frequency ratio was required as its standard, such the thirdgeneration communications UMTS (Universal Mobile Telecommunications System). Usingslot loaded two different frequencies can be achieved, f1 = 1.83 GHz and f2 = 2.07 GHz atthe feed point (16;20,5) mm with frequency ratio 1.13 and VSWR under 1.2Keywords: dual frequency, probe feed, microstrip antenna